2021
DOI: 10.1371/journal.pone.0249128
|View full text |Cite|
|
Sign up to set email alerts
|

Is the heart rate variability monitoring using the analgesia nociception index a predictor of illness severity and mortality in critically ill patients with COVID-19? A pilot study

Abstract: Introduction The analysis of heart rate variability (HRV) has proven to be an important tool for the management of autonomous nerve system in both surgical and critically ill patients. We conducted this study to show the different spectral frequency and time domain parameters of HRV as a prospective predictor for critically ill patients, and in particular for COVID-19 patients who are on mechanical ventilation. The hypothesis is that most severely ill COVID-19 patients have a depletion of the sympathetic nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
110
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(116 citation statements)
references
References 47 publications
5
110
1
Order By: Relevance
“…Its drops preceded an increase of the in ammatory marker CRP [8]. SDNN as well as other spectral parameters were shown as predictors of illness severity and mortality in critically ill patients with COVID-19 [9]. The studies of Aragón-Benedí et al…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Its drops preceded an increase of the in ammatory marker CRP [8]. SDNN as well as other spectral parameters were shown as predictors of illness severity and mortality in critically ill patients with COVID-19 [9]. The studies of Aragón-Benedí et al…”
Section: Introductionmentioning
confidence: 94%
“…Its drops preceded an increase of the in ammatory marker CRP [8]. SDNN as well as other spectral parameters were shown as predictors of illness severity and mortality in critically ill patients with COVID-19 [9]. The studies of Aragón-Benedí et al [9] and Kaliyaperumal et al [10] showed an increase in parasympathetic activity and a decrease in sympathetic activity re ecting a compensatory anti-in ammatory response in patients who died due to infection.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several epidemiological studies have shown that reduced HRV is a risk factor for all-cause mortality and morbidity (Liao et al, 2002 ), not only in cardiovascular diseases (Fang et al, 2020 ), metabolic diseases (Pavlov, 2021 ), and neurodegenerative diseases (Rangon et al, 2020 ), but also in acute respiratory distress syndrome (ARDS) (Chen et al, 2018 ), sepsis (De Castilho et al, 2018 ; Barnaby et al, 2019 ), and the severe infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Hasty et al, 2020 ; Leitzke et al, 2020 ; Aragon-Benedi et al, 2021 ; Pan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%